2019
DOI: 10.1111/bdi.12821
|View full text |Cite
|
Sign up to set email alerts
|

Current understandings of the trajectory and emerging correlates of cognitive impairment in bipolar disorder: An overview of evidence

Abstract: Objectives Cognitive dysfunction affects a significant proportion of people with bipolar disorder (BD), but the cause, trajectory and correlates of such dysfunction remains unclear. Increased understanding of these factors is required to progress treatment development for this symptom dimension. Methods This paper provides a critical overview of the literature concerning the trajectories and emerging correlates of cognitive functioning in BD. It is a narrative review in which we provide a qualitative synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 154 publications
(308 reference statements)
4
77
0
Order By: Relevance
“…Whereas we found some individuals with bipolar disorder to be characterized by cognitive stability, others experienced decline, some of them substantially. Thus, our results support the existence of both cognitive stability as well as neuroprogression in bipolar disorder, pointing to substantial cognitive heterogeneity within this disorder (Van Rheenen et al, 2020). Interestingly, we identified a relatively intact group performing largely in line with HCs.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Whereas we found some individuals with bipolar disorder to be characterized by cognitive stability, others experienced decline, some of them substantially. Thus, our results support the existence of both cognitive stability as well as neuroprogression in bipolar disorder, pointing to substantial cognitive heterogeneity within this disorder (Van Rheenen et al, 2020). Interestingly, we identified a relatively intact group performing largely in line with HCs.…”
supporting
confidence: 80%
“…Although one review concluded that bipolar disorder (affective psychosis) seems to be characterized by cognitive deficits that worsen over time after illness onset, suggesting neuroprogressive processes (Sheffield et al, 2018), other studies indicate stability of cognitive functioning over time (Demmo et al, 2018;Torres et al, 2020). Thus, it is currently unknown whether bipolar disorder is characterized by cognitive stability or progression after illness onset (Van Rheenen et al, 2020). Most likely, both notions are correct.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings can be interpreted in light of the theory of neuroprogression . Neuroprogression is marked by progressive cognitive and functioning impairment , as well as altered brain scans and biomarkers of underlying processes (inflammation, oxidative stress, apoptosis, and neurogenesis) that are evident in some cases of bipolar disorder . Recent evidence suggests that structural brain abnormalities in gray and white matter similar to those observed in age‐related neurodegenerative diseases such as dementia can also be observed in BD and may be linked to accelerated brain aging .…”
Section: Discussionmentioning
confidence: 55%
“…COVID-19 containment measures, including the physical-isolation strategies implemented by the Australian Government in late March 2020 (Vic Gov, 2020), may be especially aversive for individuals with pre-existing mood disorders. This is because they disrupt a myriad of factors critical to the management of clinical and cognitive symptoms, including easy access to in-person psychiatric care, and stability in daily routines, social rhythms and sleep patterns (Balanzá-Martínez et al, 2020;Bowen et al, 2013;Harvey et al, 2009;Van Rheenen et al, 2019). In those with a mood disorder, the occurrence of such disruptions in the context of economic volatility and financial insecurity, is likely to perpetuate the natural negative emotional responses (i.e.…”
Section: Introductionmentioning
confidence: 99%